Implementation of The Digitalization of The Accounting Information System Based On Microsoft Access - Fitri Mareta; Destia Pentiana; Depita Anggraini; Eksa Ridwansyah (Eastasouth Institute, 2026)
Technological developments in the current digital era have had a significant impact on business development, particularly in the financial sector. Digital technology has transformed the business landscape and created new ways to manage companies. A major challenge in business development is the limited use of technology in financial management, particularly in the underserved agribusiness sector. Manual financial recording processes increase the risk of recording and calculation errors and are time-consuming. This study aims to develop a Microsoft Access-based Smart Farm Accounting System software focused on digital bookkeeping and record-keeping. The Smart Farm Accounting System software can be applied to businesses in the livestock sector, taking into account the uniqueness of the agribusiness sector in accounting applications. This study is an applied research through user interviews to tailor the system development to system needs. The results of the system implementation prove that digitalization through Smart Farm Accounting improves efficiency and data accuracy.